LIPID PROFILE AND CALCIUM AND PHOSPHATE METABOLISM IN PATIENTS WITH CORONARY HEART DISEASE AND AORTIC STENOSIS - O. A. Rodicheva; S. Yu. Levashov; E. G. Volkova (Российский кардиологический журнал)
Aim. To compare the parameters of lipid profile and calcium and phosphate metabolism in patients with coronary heart disease (CHD) or CHD combined with aortic stenosis (AS). Material and methods. The study included 147 CHD patients, aged over 60, with stable angina pectoris, (functional Class (FC) I–IV) and degenerative calcific AS. The comparison group included 41 CHD patients without calcification or stenosis of aortal valve. In all participants, the parameters of lipid profile and calcium and phosphate metabolism were assessed. Results. Dyslipidemia was more prevalent in CHD patients without AS (85,4% vs. 68%). AS was linked to lower levels of total cholesterol and triglycerides. However, the combination of AS and mitral calcification was characterised by higher levels of low-density and non-high-density lipoprotein cholesterol (LDL–CH and non-HDL–CH). More severe AS was associated with decreased levels of non-HDL–CH and elevated levels of parathyroid hormone, ionized calcium, and alkaline phosphatase. There was a direct correlation between the levels of parathyroid hormone and the presence of calcific AS (r=0,532; p=0,013). Conclusion. The results obtained confirm the disturbance of lipid and calcium metabolism among patients with calcific AS, which suggests that this cardiac valve pathology could be regarded as a manifestation of ectopic calcinosis.